Nilai Estetika Selendang Pada Sindhen Wayang Kulit Purwa di Era Digitalisasi - Pitutur Tustho Gumawang; Teki Teguh Setiawan (Pusat Riset dan Inovasi Nasional, 2025)
This research examines the aesthetic value of the selendang (sash or shawl) worn by the sindhen (female singer) in wayang kulit purwa (Javanese shadow puppet) performances, and the shift in its meaning amidst the current of digitalization. The selendang, as an element of attire, functions not only as an aesthetic complement but is also laden with philosophical and symbolic meaning in Javanese culture. Traditionally, the selendang worn by a sindhen possesses aesthetic value that emanates from the choice of motifs, colors, and the way it is worn, reflecting elegance, social status, and spiritual depth. In performances, the selendang also serves as a dance prop that enhances movement and strengthens the sindhen's expression. The era of digitalization brings new challenges and opportunities for traditional performing arts, including wayang kulit purwa. This study employs a qualitative approach with literature review and observation of both live and digitally broadcasted wayang kulit performances. The results indicate that in the current digital era, a shift has occurred in several aesthetic aspects of the sindhen's selendang. There is a trend towards using more diverse and modern materials and motifs, sometimes adapting techniques like digital printing to create more visually appealing on-screen presentations. Nevertheless, the core values of the selendang as a symbol of refined character and artistic beauty are maintained, and even further explored to cater to a broader and more modern audience. The digitalization of the performance stage also influences the sindhen's interaction, where the selendang is sometimes used more dynamically